An adaptive variational algorithm for exact molecular simulations on a quantum computer - Harper R. Grimsley (Nature Portfolio, 2019)
Quantum algorithms for simulating chemical systems are limited because of the a priori assumption about the form of the target wavefunction. Here the authors present a new variational hybrid quantum-classical algorithm which allows the system being simulated to determine its own optimal state.